2021
DOI: 10.1002/jmv.26876
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of SARS‐CoV‐2 RNAemia and outcome in patients with coronavirus disease 2019

Abstract: The disease spectrum of coronavirus disease 2019 (COVID-19) varies from asymptomatic infection to critical illness and death. Identification of prognostic markers is vital for predicting progression and clinical practice. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA, known as RNAemia, has been detected in the blood.However, the potential clinical value of SARS-CoV-2 RNAemia remains unknown. We, therefore, conducted a meta-analysis using a random-effects model to estimate the pooled prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 62 publications
4
44
0
2
Order By: Relevance
“…Serum/ plasma SARS-CoV-2 viral RNA was detected in 9.4% to 74.1%, with a pooled estimate of 34% (95% CI, 26%-43%) in patients with a positive nasopharyngeal swab RT-PCR test. [7][8][9][10]17,18 Our results show that the symptoms that are more commonly found in cases with COVID-19 (fever, cough, tachypnea, and vomiting), were found at a higher percentage in the patients with SARS-CoV-2 RNAaemia. Less commonly observed symptoms (sore throat, chest pain, rhinorrhea, diarrhea, abdominal pain, and headache), were rare or not found in both the negative and positive PCR blood test groups.…”
Section: Discussionmentioning
confidence: 83%
“…Serum/ plasma SARS-CoV-2 viral RNA was detected in 9.4% to 74.1%, with a pooled estimate of 34% (95% CI, 26%-43%) in patients with a positive nasopharyngeal swab RT-PCR test. [7][8][9][10]17,18 Our results show that the symptoms that are more commonly found in cases with COVID-19 (fever, cough, tachypnea, and vomiting), were found at a higher percentage in the patients with SARS-CoV-2 RNAaemia. Less commonly observed symptoms (sore throat, chest pain, rhinorrhea, diarrhea, abdominal pain, and headache), were rare or not found in both the negative and positive PCR blood test groups.…”
Section: Discussionmentioning
confidence: 83%
“…Viremia has been independently correlated with disease severity and active clearance of viral particles is a second potential mechanism for effective therapy with Seraph100 hemoperfusion. 20 Prior research supports a direct role for heparin sulfate in SARS-CoV-2 cellular attachment and Figure 2. D-dimer values peaked at 7.1 μg/mL-FEU prior to Seraph100 treatment, declining to 2.08 μg/mL-FEU by discharge; CRP values peaked at 7.1 mg/dL prior to Seraph100 treatment, declining to 1.37 mg/dL by discharge.…”
Section: Discussionmentioning
confidence: 88%
“… 11 Recent studies demonstrated that RNAemia is associated with disease severity and unfavorable clinical outcomes. 12 , 13 This suggests that extra‐respiratory spread of SARS‐CoV‐2 contributes to systemic inflammatory responses, which are an important factor in the systemic pathogenesis of COVID‐19, including thrombosis and coagulopathy. 13 , 14…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 This suggests that extra‐respiratory spread of SARS‐CoV‐2 contributes to systemic inflammatory responses, which are an important factor in the systemic pathogenesis of COVID‐19, including thrombosis and coagulopathy. 13 , 14…”
Section: Introductionmentioning
confidence: 99%